Exploring the linkage between bacterial community composition and nitrous oxide emission under varied DO levels through the alternation of aeration rates in a lab-scale anoxic-oxic reactor. (November 2019) - Guo, Jingbo; Cong, Qiwei; Zhang, Lanhe; Meng, Lingwei; Ma, Fang; Zhang, Jian
Graphical abstract: Highlights: N2 O emission increased once after the alternation of aeration rate. A tank was the dominant location of N2 O emission. DO was critical in shaping bacterial community and determining N2 O generation. The selection of a proper DO set point was feasible for N2 O mitigation. Abstract: Dissolved oxygen (DO) level is crucial in shaping bacterial community and impacts biological nitrogen removal and nitrous oxide (N2 O) emission. Online gaseous and off-line dissolved N2 O under varying DO levels through aeration rate alternations were measured in lab-scale anoxic-oxic reactors. It showed that sharp changes in DO levels caused immediate N2 O emission increase, while the total average gaseous N2 O emission stabilized at 0.011%, 0.046%, 0.308% and 0.229% of influent nitrogen as DO in oxic tanks averaged at 0.58, 1.67, 3.2 and 6.12 mg/L, respectively. Process with an average DO concentration of 1.67 mg/L had the highest microbial diversity and relative abundances of potential denitrifers and ammonia-oxidizing bacteria (NOB), while the least ammonia-oxidizing bacteria (AOB) were detected, which contributed to efficient nitrogen removal and minor N2 O emission. In conclusion, regulation and control of denitrifiers, AOB and NOB with the determination of a proper DO set point is feasible for N2 O mitigation.